Calcineurin inhibitors ameliorate PAN‐induced podocyte injury through the NFAT–Angptl4 pathway. Issue 3 (8th September 2020) - Shen, Xiujin; Zhang, Ying; Lin, Chuan; Weng, Chunhua; Wang, Yucheng; Feng, Shi; Wang, Cuili; Shao, Xue; Lin, Weiqiang; Li, Bingjue; Wang, Haibing; Chen, Jianghua; et al.
Abstract: Podocyte injury plays a vital role in proteinuria and nephrotic syndrome. Calcineurin (CaN) inhibitors are effective in reducing proteinuria. However, their molecular mechanism is still not fully understood. Angiopoietin‐like‐4 (ANGPTL4) is a secreted protein that mediates proteinuria in podocyte‐related nephropathy. In this study, we established a puromycin aminonucleoside (PAN)‐induced minimal‐change disease (MCD) rat model and a cultured podocyte injury model. We found that CaN inhibitors protected against PAN‐induced podocyte injury, accompanied by an inhibition of Nfatc1 and Angptl4 both in vivo and in vitro . Nfatc1 overexpression and knockdown experiments indicated that Angptl4 was regulated by Nfatc1 in podocytes. ChIP assays further demonstrated that Nfatc1 increased Angptl4 expression by binding to the Angptl4 promoter. In addition, overexpression and knockdown of Angptl4 revealed that Angptl4 directly induced rearrangement of the cytoskeleton of podocytes, reduced the expression of synaptopodin, and enhanced PAN‐induced podocyte apoptosis. Furthermore, in a cohort of 83 MCD and 94 membranous nephropathy (MN) patients, we found increased expression of serum ANGPTL4 compared to 120 healthy controls, and there were close correlations between serum ANGPTL4 and Alb, urinary protein, urinary Alb, eGFR, Scr, and BUN in MCD patients. No obvious correlation was found in MN patients. Immunofluorescence studies indicated that increased ANGPTL4 in MCD and MN patients was located mostly in podocytes. In conclusion, our results demonstrate that CaN inhibitors ameliorate PAN‐induced podocyte injury by targeting Angptl4 through the NFAT pathway, and Angptl4 plays a vital role in podocyte injury and is involved in human podocyte‐related nephropathy. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.